2019
DOI: 10.1002/aur.2249
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual temporal integration and rapid temporal recalibration in adolescents and adults: Age‐related changes and its correlation with autistic traits

Abstract: Temporal structure is a key factor in determining the relatedness of multisensory stimuli. Stimuli that are close in time are more likely to be integrated into a unified perceptual representation. To investigate the age‐related developmental differences in audiovisual temporal integration and rapid temporal recalibration, we administered simultaneity judgment (SJ) tasks to a group of adolescents (11–14 years) and young adults (18–28 years). No age‐related changes were found in the width of the temporal binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Although accumulating evidence suggests that an enlarged TBW may be a shared feature in individuals with autism and schizophrenia [Zhou et al, 2018], relevant research in subclinical populations is only preliminary. For autistic traits, a few studies have found that abnormality in the audiovisual TBW may not extend to individuals with mild autistic‐like symptoms [Donohue et al, 2012; Noel, Lytle, et al, 2018; Zhou, Shi, et al, 2020], which is consistent with our findings. Another two studies, however, did find significant correlations between increased autistic traits and altered audiovisual temporal processing.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Although accumulating evidence suggests that an enlarged TBW may be a shared feature in individuals with autism and schizophrenia [Zhou et al, 2018], relevant research in subclinical populations is only preliminary. For autistic traits, a few studies have found that abnormality in the audiovisual TBW may not extend to individuals with mild autistic‐like symptoms [Donohue et al, 2012; Noel, Lytle, et al, 2018; Zhou, Shi, et al, 2020], which is consistent with our findings. Another two studies, however, did find significant correlations between increased autistic traits and altered audiovisual temporal processing.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to autistic traits, schizotypal traits are also multidimensional and some specific dimensions may be more strongly correlated with sensory processing deficits. However, another two previous studies [Muller et al, 2020; Zhou, Shi, et al, 2020] suggest that audiovisual temporal integration is not significantly correlated with any dimension of schizotypal traits. Clearly, more research with a larger sample size is needed to divide subclinical populations into various homogenous subgroups to disentangle the relationship between specific schizotypal traits and audiovisual integration ability.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Biomarker characterization will guide the detection of the most vulnerable infants benefitting from early intervention. A recent review (Zhou et al, 2020) highlighted the possibility to develop interventions to improve AV integration ability in ASD populations. Interventions based on musical trainings may provide a way to enhance audiovisual temporal precision with a cascading positive effect on social interactions and cognitive development in both clinical (Sharda et al, 2019) and in general population (Miendlarzewska & Trost, 2014).…”
Section: Discussionmentioning
confidence: 99%